The Legislator -Constituent relationship in Southern Africa: The extent to which electoral competitiveness, electoral systems and role orientation affect levels of constituency service conducted by legislators - Shearman, Leah Claire (Department of Political Studies, 2014)
The early 1990's marked the beginning of a new era for Southern Africa when a number of single party states began the transition to multiparty democratic systems. Within this process, democratic institutions were established and then have since played varied roles in normalizing of democratic norms in their respective countries. The elites who make these institutions play a vital role in maintaining democracy within these countries. This study examines their perceptions and actions in order to get a better understanding of the quality of representation and as a result the quality of democracy. More specifically the study examines how possible micro and macro level factors, such as electoral competitiveness, role orientations and electoral systems affect the level of constituency service performed by legislators in five Southern African countries (South Africa, Mozambique, Malawi, Kenya and Zambia). The majority of data used in this study comes from Module 3 of the African Legislatures Project. Electoral data was also collected from national electoral commissions and country experts. The results indicate that as a whole the electoral system has an effect on the level of constituency service conducted by legislators. Role orientation does not appear to be a factor in legislator's decision about the amount of constituency service they will perform. Electoral competition is a factor for number of countries in the study. However, the evidence shows that in some cases higher levels of electoral competitiveness actually induce legislators to perform less constituency service.